1989
DOI: 10.1007/bf01313817
|View full text |Cite
|
Sign up to set email alerts
|

Early events in arenavirus replication are sensitive to lysosomotropic compounds

Abstract: Lysosomotropic compounds (ammonium chloride, chloroquine, amantadine, monensin) effectively inhibited the replication of Pichinde, Mopeia, and Lassa viruses in BHK-21 and Vero cells. The inhibitory effect was dependent upon the time of drug addition and was most effective when the drugs were added 1 h before the viral adsorption. The drugs had no direct effect on the infectious viruses nor on adsorption of the arenaviruses. These results suggest that the arenaviruses enter cells by adsorptive endocytosis with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 8 publications
3
26
0
Order By: Relevance
“…Following receptor binding, pH-dependent viruses are routed into endosomal vesicles, where fusion between viral and cellular membranes is activated by acidification. Lysosomotropic agents, which inhibit the drop of pH in endocytic particles, were previously shown to inhibit the cell entry of several arenaviruses, including LCMV and LV, suggesting that the fusion process is triggered by low pH (6,13,20,21,48,49). We confirmed that treatment of Vero cells with bafilomycin A1 prior to and during infection inhibited infection with wt LV (data not shown).…”
Section: Biochemical and Electron Microscopic Characterization Ofsupporting
confidence: 74%
See 1 more Smart Citation
“…Following receptor binding, pH-dependent viruses are routed into endosomal vesicles, where fusion between viral and cellular membranes is activated by acidification. Lysosomotropic agents, which inhibit the drop of pH in endocytic particles, were previously shown to inhibit the cell entry of several arenaviruses, including LCMV and LV, suggesting that the fusion process is triggered by low pH (6,13,20,21,48,49). We confirmed that treatment of Vero cells with bafilomycin A1 prior to and during infection inhibited infection with wt LV (data not shown).…”
Section: Biochemical and Electron Microscopic Characterization Ofsupporting
confidence: 74%
“…The interaction of the LV GPs with their cellular receptor ␣-dystroglycan and the dependence of LV cell entry on lyso- somotropic agents are well described in the literature (6,10,21). However, in comparison to its close relative LCMV and other New World arenaviruses, characterization of the route of LV cell entry has only recently been described and seems to depend on an as-yet-uncharacterized endocytic pathway (49,61), and the only report on the pH dependence of fusion activation of the LV GP complex has only recently become public in the form of a cell-cell fusion assay (28).…”
Section: Discussionmentioning
confidence: 96%
“…Two different cellular receptors have been described, ␣-dystroglycan for the Old World and New World clade C viruses (10,30,38) and transferrin receptor type 1 (TfR1) for the New World clade B viruses (35). Binding of GP1 to a receptor results in endocytosis of the viral particle, where exposure to low pH triggers a series of conformational changes in GP2 that lead to fusion (7,11,25).…”
mentioning
confidence: 99%
“…Using lysosomotropic agents (NH4Cl, chloroquine, monensin) we [225], and others [213] documented that LASV infection was more resistant to pH increase in comparison to non-pathogenic MOPV. This is in line with findings that demonstrated a very low pH requirement for LASV fusion [218].…”
Section: Probing Lcmv-arm Versus Lcmv-we Infection With Inhibitor Drugsmentioning
confidence: 87%
“…The fusion of arenavirus proteins with cell-derived membranes is the last step of intracellular trafficking of the virus-containing vesicles. The low pHmediated fusion occurs in late endosomes/lysosomes and can be blocked by drugs raising pH in this sub-cellular compartment [225]. To assess LCMV strainspecific sensitivity to inhibitors blocking fusion with cell membrane, an established protocol was used to treat Vero cells with bafilomycin A1 to prevent acidification of the late endosomes [218].…”
Section: Probing Lcmv-arm Versus Lcmv-we Infection With Inhibitor Drugsmentioning
confidence: 99%